Mini thermoforming semi-auto machine for teaching and learning - Mastura Binti Ibrahim; Siti Aishah Binti Wahid; Sullyfaizura Binti Mohd Rawi (Education and Social Sciences Review, 2020)
Mini Thermoforming Semi-Auto Machine is a product-making machine from heated plastic sheets. This machine uses a vacuum suction method to form a product that you want to produce. This machine is designed to help and facilitate learning and teaching matters in higher education institutions where the use of this machine can reduce costs especially maintenance costs if damaged. The size of the machine is 600 mm x 500 mm which is one per fourth of the actual size in the plastic manufacturing factories. Some testing of machines and products is done. Among them is the test of lifting frame which shows the time taken for the upward movement is 4 seconds and 3.5 seconds to decrease. In addition, stress tests are also performed where the product can be perfectly formed when inhaled by vacuum. In terms of temperature the test is done by heating on the sheet or plastic sheets. The last test was made on the product, where the product was produced perfectly within 3 minutes and the temperature was 240° C. With the creation of this Mini Thermoforming Semi-Auto Machine, it is hoped that the learning and teaching process in institutions of higher learning will work better as this machine provides comfort in terms of size and prioritizes the safety of lecturers and students and is able to produce products in a short time.